Clinical Validation of a Pixon-Based Reconstruction Method Allowing a Twofold Reduction in Planar Images Time of 111In-Pentetreotide Somatostatin Receptor Scintigraphy - Thuillier, Philippe; Bourhis, David; Robin, Philippe; Keromnes, Nathalie; Schick, Ulrike; Le Roux, Pierre-Yves; Kerlan, Véronique; Chaumet-Riffaud, Philippe; Salaün, Pierre-Yves; Abgral, Ronan (Frontiers in Medicine, 2017)
Objective: The objective of this study was to evaluate the diagnostic efficacy of Pixon-based reconstruction method on planar somatostatin receptor scintigraphy (SRS). Methods: All patients with neuroendocrine tumors (NET) disease who were referred for SRS to our department during 1year period from January to December 2015 were consecutively included. Three nuclear physicians independently reviewed all the data sets of images which included conventional images (CI; 15 min/view) and processed images (PI) obtained by reconstructing the first 450s extracted data using Oncoflash® software package. Image analysis using a 3-point rating scale for abnormal uptake of 111 Indium-DTPA-Phe-octreotide in any lesion or organ was interpreted as positive, uncertain or negative for the evidence of NET disease. A maximum grade uptake of the radiotracer in the lesion was assessed by the Krenning scale method. The results of image interpretation by the two methods were considered significantly discordant when the difference in organ involvement assessment was negative versus positive or in lesion uptake was ≥ 2 grades. Agreement between the results of two methods and by different scan observers was evaluated by using Cohen κ coefficients. Results: There was no significant (p=0.403) correlation between data acquisition protocol and quality image. The rates of significant discrepancies for exam interpretation and organs involvement assessment were 2.8% and 2.6% respectively. Mean κ values revealed a good agreement for concordance between CI and PI interpretation without difference of agreement for inter/intra-observer analysis. Conclusion: Our results suggest the feasibility to use a Pixon-based reconstruction method for SRS planar images allowing a two-fold reduction of acquisition time and without significant alteration of image quality or on image interpretation.